Iron and calcium nutrition interventions among Vietnamese women - Nguyen, Linh Thuy; Pham, Tho Anh; Thanh Ta, Nga; Komatsu, Yoshinori; Tran, Thao Phuong (Intelektual Pustaka Media Utama, 2023)
Iron and calcium deficiencies remain a concern amongst working-age women in low to middle-income countries. This study aimed to evaluate the effect of nutritional intervention on the improvement of the iron status and calcium intake of this population. Non-pregnant workers at a company were divided into two groups. The intervention group (n=118) received nutritional intervention including nutritional education and an 8-week course of oral nutritional supplements (ONS). The control group (n=106) did not receive any intervention. Nutritional assessment, level of Hb concentration, serum iron, and ferritin were taken at baseline and after eight weeks. The results showed iron and calcium intake increased significantly in the intervention group. The effective intervention of serum iron was 33.3%. In conclusion, nutritional intervention such as nutritional education and ONS consumption is effective for improving iron status and calcium intake in working-age women.